An Analysis of Buddhist Ethics in Synshai Literature - Bamrungphak, Sowit (Journal of International Buddhist Studies, 2017)
The purposes of the study were 1) to study the problems of ethics and well-related practice in Synshai Literature, 2) to study the Buddhist ethics in Synshai Literature, and 3) to analyze the considerable standard and ethical objectives of Synshai Literature. This study was a documentary research in which the data collection was by studying the Palm-leaf manuscripts 2016 of Synshai Literature of Khonkaen Synshai Literature transcribed by Mr. Bunkirt Phimvaramethakul and colleagues, and secondary data was by other Synshai manuscripts. The research method was logical consider and analysis, synthesis of all data for new knowledge, and used Descriptive Analysis to present the research result. The research results were found that an ethical problem in Synshai literature involved with stealing, getting married with many wives, using black magic, and committing adultery. Well-related practice among people was divided into two levels: a domestic level and a relative level. To describe such an ethical problem depended upon Buddhist ethics which was Buddhist knowledge dealt with desirable behavior or manners that people should follow under the standard of Five Precepts. A morality of precept or Dhamma of precept and Buddhist morality consisted of suffering, sexual craving, and previous action under the moral standard of Ten Virtues of the King, and Eightfold Noble Path. The Buddhist doctrine for national management under the standard of ethics stated to the desirable and undesirable ethics. The standard of ethics consideration was divided into two types: 1) the standard relating to Buddhism, i.e. an intention or a purpose to make things wholesome or unwholesome according to moral laws, and 2) the associated standard or the inferior standard which was dealt with conscience principle, what is good or bad, knowing what should behave, and experienced persons’ resolution referring to a brainy person in governing the expression of people in community. The purpose of action in Synshai Literature was to close the gap between a person and associated people and be adorable of a mother, a father, a son and a daughter, and so on.